Reliable Fit-Up of Steel I-Girder Bridges. Issue 1 (2017) - Coletti, Domenic A.; White, Donald W.; Nguyen, Thanh V.; Chavel, Brandon W.; Grubb, Michael A.; Boring, Calvin G.
This paper summarizes recently completed research supporting the development of improved design, detailing, and erection guidelines to ensure reliable fit-up of skewed or curved (or both) steel I-girder bridges. Twenty-one bridges, including several with multiple framing arrangements, were analyzed to provide quantitative support for, and refinements to, guidelines produced by an affiliated National Steel Bridge Alliance Steel Bridge Collaboration Task Group. The quantitative data of this research support recommended fit conditions (i.e., cross-frame detailing methods) as a function of the bridge geometry. Forces required to assemble the steel during erection were evaluated, and difficult cases were highlighted. Suggested erection considerations to facilitate fit-up were provided. In addition, the research investigated and specified beneficial staggered cross-frame arrangements for straight skewed bridges, as well as framing arrangements around bearing lines at interior piers in continuous-span bridges. The research emphasized identification of the impacts of the chosen fit conditions on girder elevations, girder layovers, cross-frame forces, girder stresses, and vertical reactions in completed bridge systems. This paper provides simplified methods of accounting for steel dead-load fit and total dead-load fit detailing effects. Procedures are provided for direct calculation of the locked-in forces due to steel dead-load fit and total dead-load fit detailing in cases in which a more precise calculation of these effects may be beneficial. Construction inspection best practices are recommended to ensure that the erected geometry sufficiently meets the specified fit conditions, and design specification provisions that synthesize the key guidelines are recommended.